Technology-enhanced digital game-based learning for environmental literacy: catalyzing attitude change in learners - Chuang, Tsung-Yen; Tsai, Szu-Kai; Lu, Yu-Hsuan (Frontiers in Education, 2025)
Recently, various approaches have been adopted to cultivate environmental literacy, and prior studies have confirmed the value of digital games in this domain. Nonetheless, concrete discussions of specific elements such as environmental sensitivity and attitude remain limited. Accordingly, the present quasi-experimental study investigates whether Digital Game-Based Learning (DGBL) can enhance the environmental literacy of Taiwanese elementary school students. Thirty-four sixth-graders were assigned to a DGBL group (n = 17) and a Web group (n = 17). Quantitative data were collected with an Environmental Literacy Scale covering knowledge, sensitivity, and attitude, while qualitative insights were gathered through semi-structured interviews. Post-test scores were analyzed via ANCOVA with pre-test scores as covariates. Results indicate that the DGBL intervention significantly improved students’ environmental knowledge and attitude, whereas gains in environmental sensitivity, though evident, did not reach statistical significance. Qualitative responses echoed these findings, suggesting that immersive gameplay fosters deeper affective engagement with ecological issues even when measurable sensitivity improvements are modest.